2000
DOI: 10.1053/jhep.2000.19340
|View full text |Cite
|
Sign up to set email alerts
|

Early Identification of Recipients With Progressive Histologic Recurrence of Hepatitis C After Liver Transplantation

Abstract: Approximately half of patients undergoing liver transplantation (LT) for hepatitis C virus (HCV) develop histologic evidence of recurrence within the first postoperative year. Early identification of recipients at risk for more severe recurrence of HCV may be useful in selecting patients for antiviral therapy. We determined whether recipients at greatest risk for more severe recurrence of HCV can be identified by pre-and/or early post-LT HCV-RNA levels in serum or tissue. Serum and tissue samples were prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
124
2
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(134 citation statements)
references
References 41 publications
7
124
2
1
Order By: Relevance
“…3,9,13,[25][26][27] In addition, timing of recurrence to progressive disease (early recurrence) also seems associated with a worse prognosis. 28,29 …”
Section: Histologic Changesmentioning
confidence: 99%
“…3,9,13,[25][26][27] In addition, timing of recurrence to progressive disease (early recurrence) also seems associated with a worse prognosis. 28,29 …”
Section: Histologic Changesmentioning
confidence: 99%
“…5 Furthermore, two studies showed that a pulse of methylprednisolone therapy increased serum HCV levels by one log before returning to pre-pulse levels during a 2-week period. 6,16 Thus, at this early stage of infection, additional CS therapy seems to be associated with greater viral loads, which may have important implications concerning HCV-related allograft injury. …”
Section: Effect Of Immunosuppression Level On Early Hcv Recurrencementioning
confidence: 99%
“…There is evidence indicating that pre-OLT HCV RNA titers and initial levels of HCV RNA intrahepatic replication are predictive of subsequent liver disease progression. 25,28,33 This argument also is supported indirectly by the efficacy of early treatment in both human immunodeficiency virus and HCV acute infections.…”
Section: Discussionmentioning
confidence: 95%
“…A greater frequency of hepatitis recurrence was observed in patients with reduced CD4 ϩ T-cell response. 32 Greater levels of intrahepatic and circulating HCV RNA have been detected in patients with hepatitis recurrence, 25,33,34 and greater HVR1 variation has been reported in asymptomatic HCV carriers than in patients with progressive chronic hepatitis. 6 Finally, there is extensive clinical evidence that steroid treatment and stronger immunosuppression regimens negatively affect post-OLT recurrent hepatitis.…”
Section: Discussionmentioning
confidence: 99%